FACTORS RELATED TO CONTRACT EMPLOYEES’S JOB SATISFACTION IN CONSTRUCTION COMPANY X, SEMARANG CITY - Ariska Vinanti Sadya; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Job satisfaction is the attitude of the worker to the work he does. Job satisfaction must be considered by human resource managers because it is related to level of health, performance, sustainability of labor (presistence) and productivity. The purpose of this study is to analyze the correlation between perception of job, supervision, salary, promotion dan co-worker with job satisfaction of contract employees in Construction Company X, Semarang City. This research is analytical descriptive research using cross-sectional. The population and sample in this research are 40 contract employees of Construction Company X. The instrument that used in this research are Minnesota Satisfaction Questionaire (to measure job satisfaction)dan Job Descriptive Index (to measure perception of job, supervision, salary, promotion dan co-worker). As many as 47,5% contract employees were satisfied with their work. The result showed that there is correlation between perception of job (sig 0,001), supervision (sig 0,001) and salary (0,001) with job satisfaction. There is no correlation between promotion (sig 0,115) and co-worker (sig 0,113) with job satisfaction. To increase contract employee’s satisfaction, the company should give relaxation facilities as a tool for increase good relationship, listen and resolve employee complaints, give reward to employee and stakeholders approach their employees.